The Ethics of Social Life in Sidonie de la Houssaye’s Louisiana Tales - Christine A. Jones (Humanities, 2025)
Creole writer Sidonie de la Houssaye (1820–1894) registered the threat of anglophone dominance after the Civil War on behalf of a host of characters drawn from the geographies and ideologies in and around her home in Louisiana. Her little-known literary tales depict the period as a cultural and linguistic border zone. In addition to the texture of Louisiana French and Creole heritage, the tales depict the vexed social dynamics of prejudice and fragility. In the context of this special issue on good and evil, the poorly known children’s tales offer insight into these pernicious tensions that persisted under the surface of moral victory after the Civil War. La Houssaye’s lessons for children take up the moral panic of a Louisiana reckoning with its legacies of racial violence and cultural erasure. This article argues that morality in these tales takes shape in interpersonal practices that can be learned to heal social ills. What I have called La Houssaye’s “ethics of social life” relies on education rather than condemnation to redefine human bonds. If a broader lesson emerges from the stories taken together, it suggests that structural change is slow to heal cultural wounds. We must ourselves be the agents of a healthier community.